Dynamic assessment of a FRP suspension footbridge through field testing and finite element modelling - Votsis, Renos; Stratford, Tim J.; Chryssanthopoulos, Marios K.; Tantele, Elia (My University, 2017)
The use of advanced fibre composite materials in bridge engineering offers alternative solutions to structural problems compared to traditional construction materials. Advanced composite or fibre reinforced polymer (FRP) materials have high strength to weight ratios, which can be especially beneficial where dead load or material handling considerations govern a design. However, the reduced weight and stiffness of FRP footbridges results in generally poorer dynamic performance, and vibration serviceability is likely to govern their design to avoid the footbridge being "too lively". This study investigates the dynamic behaviour of the 51.3 m span Wilcott FRP suspension footbridge. The assessment is performed through a combination of field testing and finite element analysis, and the measured performance of the bridge is being used to calibrate the model through an updating procedure. The resulting updated model allowed detailed interpretation of the results. It showed that nonstructural members such as the parapets can influence the dynamic behaviour of slender, lightweight footbridges, and consequently their contribution must be included during the dynamic assessment of a structure. The test data showed that the FRP footbridge is prone to pedestrian induced vibrations, although the measured response levels were lower than limits specified in relevant standards.
Keywords: Dynamic test; Fibre reinforced polymer; Finite element method; Vibration serviceability; Footbridges